2013
DOI: 10.1016/j.jaac.2012.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Late Preterm Birth, Maternal Depression, and Risk of Preschool Psychiatric Disorders

Abstract: Objective Preterm children are at greater risk for psychiatric disorders than their term-born peers including anxiety disorders and ADHD. Prior research has focused primarily on children born at early gestational ages. Less is known about the rate of psychiatric disorders among late preterm or early term children. Additionally, whether a history of maternal depression, also associated with prematurity, impacts the risk for psychiatric disorders remains underexplored. Method Preschoolers between ages 3 and 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 60 publications
2
34
0
Order By: Relevance
“…Correspondingly, a previous study showed that moderate or late preterm birth predicted an increased risk of suicides and/or suicide attempts in young adulthood (Lindström et al 2009) but whether this effect was more pronounced on committed or attempted suicide was not specified. However, in contrast to studies in younger cohorts showing predisposing effects of late preterm birth on any mental disorder and on internalizing disorders in childhood (Talge et al 2010;Rogers et al 2013), or of moderate or late preterm birth on severe mental disorders across diagnostic boundaries in young adulthood (Moster et al 2008;Lindström et al 2009;Nosarti et al 2012), Table 3. Gestational age and severe mental disorders.…”
Section: Discussionmentioning
confidence: 89%
“…Correspondingly, a previous study showed that moderate or late preterm birth predicted an increased risk of suicides and/or suicide attempts in young adulthood (Lindström et al 2009) but whether this effect was more pronounced on committed or attempted suicide was not specified. However, in contrast to studies in younger cohorts showing predisposing effects of late preterm birth on any mental disorder and on internalizing disorders in childhood (Talge et al 2010;Rogers et al 2013), or of moderate or late preterm birth on severe mental disorders across diagnostic boundaries in young adulthood (Moster et al 2008;Lindström et al 2009;Nosarti et al 2012), Table 3. Gestational age and severe mental disorders.…”
Section: Discussionmentioning
confidence: 89%
“…(20,21) We have also previously noted increased rates of psychiatric disorders, including a four-fold risk for anxiety disorders, at preschool age among LP children in the cohort to be examined in the analyses presented here. (22) Elevated rates of generalized anxiety disorder and separation anxiety disorders were found in this group. While we found these early childhood anxiety disorders in LP children were mediated by maternal depression, underlying neurodevelopmental differences could confer additional risk.…”
mentioning
confidence: 76%
“…Furthermore, in preterm children whose mother experienced the perinatal period as stressful, the impact of early adversities on behavioural problems and psychiatric disorders at preschool age is greater [30,35,36]. Even mothers of children born late preterm (34-37 weeks gestation) experienced significantly higher levels of emotional stress than mothers of term-born children [26].…”
Section: Discussionmentioning
confidence: 99%